Disaster-Ready School Preparedness In Facing Flood Disasters At Sma Negeri 10, Sigi Regency - Nurvita Nurvita; Risma Fadhila Arsy; Haslita Rahmawati Hasan; Suwarni Suwarni (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to determine the level of school preparedness at SMA Negeri 10 in facing flood disasters in Rogo Village, South Dolo Sub-district, Sigi Regency. This research uses a qualitative descriptive approach with questionnaire, observation, and documentation methods. School preparedness parameters are 1) Knowledge Attitude or Attitude and Action, 2) Policy Statement or School Policy, 3) Emergency Planning or Emergency Response Plan, and 4) Resource Mobilization Capacity or Resource Mobilization, were collected using questionnaires and analyzed descriptively. Based on data processing and analysis, it was found that the preparedness of the entire School Community (KS) of SMA Negeri 10 Sigi based on a combination of all parameters was in the low category with an index value of 54.14%. It was found that the value of the knowledge parameter was in the medium category with an index of 75.81%, low school policy with an index number of 7.41, low emergency response plan with an index of 50.43, low disaster warning with an index value of 41.23 and resource mobilization in the medium category with an index of 55.74. Thus it can be concluded that SMA Negeri 10 Sigi has not provided educational policies or programs related to flood disaster preparedness in schools, allocated a special budget for school preparedness, policies to integrate flood disaster preparedness materials into relevant subjects and activities. It is necessary to get the attention of the government in this case the District Education Office to immediately carry out regulations and special assistance to prepare disaster preparedness schools, especially at SMAN 10 Sigi and generally in schools located in flood-prone areas.